Combination of arsenic trioxide and Dasatinib: a new strategy to treat Philadelphia chromosome‐positive acute lymphoblastic leukaemia. Issue 3 (20th December 2017) - Wang, Tao; Cheng, Chunyan; Peng, Lijun; Gao, Mengqing; Xi, Mengping; Rousseaux, Sophie; Khochbin, Saadi; Wang, Jin; Mi, Jianqing
Abstract: Tyrosine kinase inhibitors (TKIs) have significantly improved the prognosis of Philadelphia chromosome‐positive acute lymphoblastic leukaemia (Ph + ALL), one of the most common and aggressive forms of haematological malignancies. However, TKI resistance has remained an unsolved issue. In this study, we investigate the impact of adding arsenic trioxide (ATO) on the action of Dasatinib, a second‐generation TKI, in Ph + ALL. We show that ATO cooperates with Dasatinib in both TKI‐sensitive and resistant Ph + ALL cell lines to increase apoptosis and we unravel the underlying mechanisms. Indeed, combining ATO and Dasatinib leads to severe cell apoptosis by activating the UPR apoptotic IRE1/JNK/PUMA axis, while neutralizing the UPR ATF4‐dependent anti‐apoptotic axis, activated by ATO alone. Additionally, ATO and Dasatinib in combination repress the expression of several genes, which we previously showed to be associated with shorter survival probability in ALL patients. Overall these data support the use of ATO in combination with Dasatinib as a novel therapeutic regimen for Ph + ALL patients.